Geographic tongue. A possible manifestation of atopic dermatitis. - Menni, S.; Saleh, F.; Bigardi, A. (European Journal of Pediatric Dermatology, 2018)
Geographic tongue (GT) is a very frequent disorder in children. The Authors investigated the population nocking to their outpatient department of pediatric dermatology during two years. They found a significant relationship between GT and atopic dermatitis. Moreover, the age prevalence of these two disorders was rather superimposable. These findings confirm many reports of the relevant literature regarding a significant relationship between GT and atopy. Morcover, these findings suggest that GT should be included among the minor diagnostic criteria of atopic dermatitis.